A BIBLIOMETRIC ANALYSIS OF USING WEB 2.0s IN EDUCATIONAL RESEARCH ARE - Kaya, Vildan Donmuş (My University, 2022)
The purpose of present study is to reveal the tendency towards Web 2.0s in the educational research area with the analysis of bibliometric mapping. As of July 5th 2021, the 786 studies have been retrieved from in the Web of Science database, and are included in the analysis. VOSviewer was used for the analysis of bibliometric mapping. As a result of the analysis of bibliometric mapping, it was concluded that the most effective countries in Web 2.0s in the educational research area are the USA, England, and Spain. According to the keyword co-occurrence analysis, technology, social media, collaborative learning, e-learning, and higher education keywords stand out on Web 2.0s in the educational research area. It was found that Timothy J. Newby is the most productive researcher. It can be concluded that the most effective researches are higher education researches. According to the analyses conducted in the context of journals, Australasian Journal of Educational Technology”, “Interactive Learning Environments”, and “Internet and Higher Education” were the most contributing journals.
Keywords: Bilgisayar Bilimleri; Yazılım Mühendisliği; Eğitim; Eğitim Araştırmaları